Potret Wajah Masyarakat Digital Indonesia - Engkus Kuswarno (Jurnal Communicate, 2015)
The aim of this study was to determine the facial portrait of the people in Indonesia. Where, development of communication technology so quickly spread throughout the joint community. Software applications (social networks: messages bb, bb group, fb, twitter), communication devices (smart phones, tablet) as well as the availability of broadband access (broadband) became the catalyst for the consumer is ready to connect at any time. This type of research is descriptive. In demographic, online community in Indonesia in terms of gender, it is known that men 51.5% and women 48.4%. Although almost equal, but the population of men more than women. The figures are almost the same as the people who live in urban areas than rural areas. Internet users in urban communities 51% and 49% rural. The interesting thing is the villagers had almost following the urban community in the use of the Internet. It shows also that online penetration through the countryside to the IT infrastructure in Indonesia is quite high